2001
DOI: 10.21236/ada525861
|View full text |Cite
|
Sign up to set email alerts
|

Using a Community of Intelligent Synthetic Entities to Support Operational Team Training

Abstract: A strong need exists for a simulation-based means to provide individuals in deployed settings teamwork and cross-platform coordination skills training in realistic, mission-oriented scenarios. This need can be met by using advanced human behavioral representation technology to provide synthetic teammates and collateral entities operating within a sophisticated synthetic battlespace. When combined with a full range of automated, intelligent agent-based instructional support capabilities including real-time perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The development of DMT programs in the military has resulted in two training platforms that utilize simulated training scenarios and virtual teammates, or cognitive agents, and actual military personnel: Synthetic Cognition for Operational Team Training (SCOTT) (Zachary et al, 2001) and Synthetic Teammates for Realtime Anywhere Training and Assessment (STRATA) (Bell, 2003). Users are able to log in to a secure network using a user name and password from anywhere in the world and are placed into a training scenario that will develop the knowledge and skills that are needed according to their training profile.…”
Section: Distributed Team Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of DMT programs in the military has resulted in two training platforms that utilize simulated training scenarios and virtual teammates, or cognitive agents, and actual military personnel: Synthetic Cognition for Operational Team Training (SCOTT) (Zachary et al, 2001) and Synthetic Teammates for Realtime Anywhere Training and Assessment (STRATA) (Bell, 2003). Users are able to log in to a secure network using a user name and password from anywhere in the world and are placed into a training scenario that will develop the knowledge and skills that are needed according to their training profile.…”
Section: Distributed Team Trainingmentioning
confidence: 99%
“…During each of the simulated exercises, the DSS could aid the trainee in the decision-making process and provide feedback for each decision that is made. This strategy has been implemented most recently in the military with the development of Synthetic Cognition for Operational Team Training (SCOTT) (Zachary et al, 2001) and Synthetic Teammates for Realtime Anywhere Training and Assessment (STRATA) (Bell, 2003). These distributed-based training programs offer real-time strategy training and feedback via DSS in a secure networked training environment.…”
Section: Training Evaluation 17 Consider Evaluation Design Issuesmentioning
confidence: 99%
“…Existing studies proved that the replacement of humans with intelligent synthetic agents to train aviation teams would not attribute any loss in training efficiency (Demir et al, 2015;Zachary, Santarelli, Lyons, Bergondy, & Johnston, 2001). In a generic sense, a synthetic agent or intelligent software agent is defined as "Complex software entities that carry out some set of operations on behalf of a user with some degree of autonomy" (Franklin & Graesser, 1997).…”
Section: Research Backgroundmentioning
confidence: 99%
“…A voice-based SA (VBSA) uses voice interaction as the primary communication mode. Many SA techniques that are task-specific are being implemented by different organizations (Ball et al, 2010;Zachary et al, 2001). Indeed, the developed VBSA is also a task-specific SA.…”
Section: Voice-based Synthetic Assistantmentioning
confidence: 99%
“…Previous research has shown the benefits of developing synthetic agents to support team training (Jones et al 1999;Tambe et al 1995;Zachary et al 2001) and for evaluation of computer interfaces (Byrne et al 1994;Ritter et al 2002). The main objective of the Synthetic Teammate project is to develop synthetic agents capable of being integrated into team training simulations.…”
Section: Project Overviewmentioning
confidence: 99%